The relationship between bruxism symptoms and temporomandibular disorders and anxiety caused by the COVID-19 pandemic: a literature review (Research, Society and Development, 2021)
The aim of the present study was to perform a literature review about the relationship between the symptoms of bruxism and temporomandibular disorders and the anxiety caused by the pandemic of COVID-19. A review of studies available in the literature was performed through bibliographic search in the electronic databases Pubmed / Medline and Google academic. The following descriptors were used for the research: “Pandemic” AND “Covid-19” AND “Bruxism” AND “Temporomandibular disorder”. Another search strategy was to manually search the reference lists of selected articles. As inclusion criteria, articles written in English and Portuguese were adopted; those that fit the work focus and the most relevant in terms of outlining the desired information. The global consequences of the COVID-19 pandemic are diverse and also involve the psychological aspect. The COVID-19 pandemic may be associated with an increase in psychological symptoms such as anxiety and depression due to the period of social isolation. These symptoms are associated with temporomandibular disorders and bruxism leading to the appearance and development of both conditions.